Exposure to Korean Pop Culture (K-Pop) And Tiktok Usage on The Shift in Cultural Preferences (Drama and Music) Among Generation Z - Lia Rismawati; Hasan Asari (Department of Tadris IPS FITK UIN Siber Syekh Nurjati Cirebon, 2026)
The development of social media has accelerated the spread of global culture, including Korean pop culture (K-Pop), among Generation Z. However, research on exposure to K-Pop culture and the use of TikTok on changes in Generation Z's cultural preferences in Medan City is still limited. This study aims to analyze the use of TikTok and exposure to K-Pop culture on changes in Generation Z's cultural preferences in Medan City. The study used a qualitative descriptive approach with a sample of 10 Generation Z informants aged 17–25 years selected using purposive sampling. Data were collected through interviews, observations, and documentation using interview guidelines, observation sheets, and research documentation. Data analysis was carried out through data reduction, narrative presentation, and conclusions. The results show that TikTok, through its For You Page (FYP) feature, increases exposure to K-Pop, thereby influencing Generation Z's preferences for Korean dramas, music, and culture. The implications of this study demonstrate the importance of utilizing digital media in introducing local culture to maintain Generation Z's interest.